Vulnerability Life of Female Farmers in Rindu Hati Village Taba Penanjung District Bengkulu Tengah Regency of Bengkulu Province Indonesia - Yessilia Osira (Asian Social Work Journal, 2019)
Female Farmers in Rindu Hati Village not only help their husbands or family heads to make a living to increase family income which is also expected to improve the level of family welfare, but also take care of the household, such as childcare and other domestic work. This condition makes female farmers have some vulnerability in their lives. There are three components of vulnerability affecting adaptation strategies of female farmers in their lives: 1) the level of exposure, i.e. the extent to which female farmers intersects with the disorder. 2) The level of sensitivity, defined as the effect or impact of the problem or disorder received either directly or indirectly by the female farmers. 3) Adaptability (capacity of response), is the female farmers ability to respond disturbances, balance the potential impacts that will occur, take advantage of opportunities, and fused with the consequences that may arise from a change (Gallopin 2006). This study used the descriptive qualitative design, to examine the vulnerability life of female farmers. Through interviews and observation of 24 informants who then analyzed, the researchers got the conclusions: 1) Female farmers are mostly dominated by those over 40 years old. Most of them have elementary school education, with dependents living 3 to 7 people. 2) Female farmers have experience vulnerability in the aspects of education, health aspects, and economic aspects. Vulnerability of life in these three aspects results in female farmers and their families experiencing various problems of lack of knowledge and skills, disruption of health, and low income to meet their daily needs. Nevertheless, the results of the study also show that these female farmers have potential and resources that can be utilized in dealing with vulnerabilities and life problems, namely social capital in the form of family values and mutual cooperation that are still strong in Rindu Hati Village. Based on the vulnerability and potential as well as the available source system, it is recommended that there be efforts to empower or develop the capacity of female farmers so that they are able to face the vulnerability of life while at the same time increasing their welfare.